Nonequilibrium dissipation in living oocytes. (22nd December 2016) - Fodor, É.; Ahmed, W. W.; Almonacid, M.; Bussonnier, M.; Gov, N. S.; Verlhac, M.-H.; Betz, T.; Visco, P.; van Wijland, F.
Abstract: Living organisms are inherently out-of-equilibrium systems. We employ recent developments in stochastic energetics and rely on a minimal microscopic model to predict the amount of mechanical energy dissipated by such dynamics. Our model includes complex rheological effects and nonequilibrium stochastic forces. By performing active microrheology and tracking micron-sized vesicles in the cytoplasm of living oocytes, we provide unprecedented measurements of the spectrum of dissipated energy. We show that our model is fully consistent with the experimental data, and we use it to offer predictions for the injection and dissipation energy scales involved in active fluctuations.